A community based, bottom-up, multi-pronged, technology integrated approach to enhance tuberculosis related awareness and treatment adherence in Uganda: The ACTS model - Stavia Turyahabwe; Srikrishna Sulgodu Ramachandra; Subhi Quraishi; Ilmana Fasih; Hilmi Quraishi; Palavardhan Peddapalegani; Akram Ahmad (PLoS ONE, 2025)
Background Tuberculosis (TB) is still a major public health challenge globally and Uganda is one among the top 30 high TB burden countries. One of the key factors determining TB treatment success rates and thereby Cure Rates is the adherence to TB treatment, which is still a major challenge globally. WHO DOTS (Directly Observed Treatment Short course) strategy has several limitations and WHO End TB Strategy 2017 suggests a suite of new interventions to improve adherence. Objectives of the study a. To present the development and design of ZMQ’s Active Care and Treatment Strategy (ACTS) Model. b. To present the results of a pilot study done using the ACTS Model. c. To compare Treatment Adherence Rates between DOTS and Video Observed Treatment (VOT) in the four districts of Uganda. Materials and methods Includes presenting the ACTS Model, a pilot study to assess the AGB and ACF by way of a pre-post (Quasi-experimental) study (n = 1000) to assess the impact of AGB exercises, Focus Group Discussions (FGD) to get insights into factors contributing to treatment non-adherence and a comparison between VOT (n = 800) vs. DOTS for treatment adherence. Results There was a significant improvement (p<0.01) in knowledge and awareness levels of community members post the AGB exercises which included creating awareness using digital storytelling, house visits and more. TB treatment adherence rates among TB patients using VOT was significantly better (p<0.01) than those using DOTS. Conclusion AGB and ACF play a significant role in creating more awareness amongst the community members and identifying more number of cases. It helps in better treatment seeking behaviour, improved treatment rates and treatment adherence rates and in turn better cure rates. VOT is far more superior to DOTS, as a strategy for TB treatment adherence and VOT decreases the resources required in terms of human resource, time and money and is also a more sustainable mode of treatment adherence.